Compound C, a Broad Kinase Inhibitor Alters Metabolic Fingerprinting of Extra Cellular Matrix Detached Cancer Cells - Shait Mohammed, Mohammed Razeeth; Alghamdi, Raed Ahmed; Alzahrani, Abdulaziz Musa; Zamzami, Mazin A.; Choudhry, Hani; Khan, Mohammad Imran (Frontiers in Oncology, 2021)
Most of the cancer related deaths are caused mainly by metastasis. Therefore, it is highly important to unfold the major mechanisms governing metastasis process in cancer. Throughout the metastatic cascade, cells need the ability to survive without attachment to neighboring cells and the original Extra Cellular Matrix (ECM). Recent reports showed that loss of ECM attachment shifts cancer cell metabolism towards glycolysis mostly through hypoxia. However, AMPK, another important metabolic regulator was also found to be upregulated under ECM detached conditions. Therefore, in this work we aimed to understand the metabolic consequences of AMPK inhibition in ECM detached cancer cells. Results showed that inhibition of AMPK with established inhibitor compound C impacts glycolysis as evident by increased levels of pyruvate, but reduces its conversion to lactate thereby negatively regulating the warburg effect. Simultaneously, AMPK inhibition induces blocks at multiple levels in TCA cycle as evident from accumulation of various TCA metabolites. Interestingly AMPK inhibition significantly reduces glutamine and reduced glutathione levels, suggesting loss of antioxidant potential of ECM detached cancer cells. Further, we found increased in metabolites associated with nucleotide synthesis, one carbon metabolism and PPP pathway during AMPK inhibition in ECM detached cells. Finally, we also found induction in metabolites associated with DNA damage in ECM detached cancer cells during AMPK inhibition, suggesting DNA damage regulatory role of AMPK. Overall, our results showed that AMPK inhibition represses pyruvate to lactate conversion, reduces antioxidant potential and invokes DNA damage in ECM detached cancer cells. Our data provides a comprehensive metabolic map of ECM detached cancer cells during AMPK inhibition and can be exploited for designing new combinational therapies to eradicate ECM detached cancer cells.